2022
DOI: 10.1093/cid/ciac327
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus Disease 2019 Vaccine Boosting in Previously Infected or Vaccinated Individuals

Abstract: Background The purpose of this study was to evaluate whether boosting previously infected or vaccinated healthcare personnel with a vaccine developed for an earlier variant of SARS-CoV-2 protects against the Omicron variant. Methods Employees of Cleveland Clinic previously infected with or vaccinated against COVID-19, and working in Ohio the day the Omicron variant was declared a variant of concern, were included. The cumulat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 8 publications
3
25
1
Order By: Relevance
“…Sixteen unique articles reporting data for 26 studies were included for analysis. [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] Seven articles reported data for multiple studies, defined by multiple sets of study methods and independent populations with unique estimates of protection. Eleven studies reported on prior infection and 15 studies reported on hybrid immunity, which included six reporting on both.…”
Section: Resultsmentioning
confidence: 99%
“…Sixteen unique articles reporting data for 26 studies were included for analysis. [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] Seven articles reported data for multiple studies, defined by multiple sets of study methods and independent populations with unique estimates of protection. Eleven studies reported on prior infection and 15 studies reported on hybrid immunity, which included six reporting on both.…”
Section: Resultsmentioning
confidence: 99%
“…A large study found, in an adjusted analysis, that those who had an Omicron variant infection after previously receiving three doses of vaccine had a higher risk of reinfection than those who had an Omicron variant infection after previously receiving two doses of vaccine [22]. Another study found, in multivariable analysis, that receipt of two or three doses of a mRNA vaccine following prior COVID-19 was associated with a higher risk of reinfection than receipt of a single dose [7]. We still have a lot to learn about protection from COVID-19 vaccination, and in addition to a vaccine's effectiveness, it is important to examine whether multiple vaccine doses given over time may not be having the beneficial effect that is generally assumed.…”
Section: Discussionmentioning
confidence: 99%
“…A large study found, in an adjusted analysis, that those who had an Omicron variant infection after previously receiving three doses of vaccine had a higher risk of reinfection than those who had an Omicron variant infection after previously receiving two doses of vaccine [22]. Another study found, in multivariable analysis, that receipt of two or three doses of a mRNA vaccine following prior COVID-19 was associated with a higher risk of reinfection than receipt of a single dose [7]. Immune imprinting from prior exposure to different antigens in a prior vaccine [22,23], and class switch towards non-inflammatory spike-specific IgG4 antibodies after repeated SARS-CoV-2 mRNA vaccination [24], have been suggested as possible mechanisms by why prior vaccine may provide less protection than expected.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations